Community-Based Intervention: A Case Study of Pantoloan Boya Village Community Through the Rehabilitation Field Program of National Narcotics Agency, Palu City - Arwan Arwan; Sadli Syam; Rasyika Nurul Fadjriah; Sulfiyanti Sulfiyanti; Muhammad Ryman Napirah (Media Publikasi Cendekia Indonesia, 2023)
Drug abuse is becoming more of a threat and garnering global attention, particularly in parts of Southeast Asia. The drug issue in Indonesia is urgent and multifaceted. In 2019, Central Sulawesi ranked fourth in Indonesia for the highest rate of drug abuse, with 3.30% of the population, or the equivalent of 61,857 drug users. According to research, Palu City has the highest rate of drug abuse in Central Sulawesi province. The purpose of this research was to find out how the Community-Based Intervention (CBI) Program is being implemented in the Rehabilitation Sector of BNN Kota Palu in Pantoloan Boya Village. The method used in this study was qualitative. This study used a purposive sample strategy to select 7 informants. The results showed that the mapping was carried out by RW (Hamlet)/RT (Neighbourhood)-based Recovery Agents (RA) with minimal Human Resources (HR) and clients who participated in limited interventions. Outreach is the delivery of information and approaches to the community, families, and drug users. This study's recommendations include mapping to expand HR capacity, in this case, RAs and clients, so that the program works more efficiently. Increase client compliance in group and individual meetings as part of outreach. Recovery services are being provided by pushing for the continuation of CBI's activities in Pantoloan Boya Village